Diffusion of Innovation: The Hologram Shape of President Jokowis Appearance at Smart Citizen Day 2019 Event - Idama, Felicia Debora; Ansari, Ambar Nurul; Winindyasari, Mahaningrum (The Indonesian Journal of Social Studies, 2020)
The hologram has been considered as communication medium, which is also in fact, this technology has been adopted in varied occasions and purposes as well as to provide a showcase of a technology advancement. Smart Citizen Day 2019 has been noted quite a breakthrough since instead of having an opening video or live speech from President Joko Widodo, the Ministry of Secretary State has come to a decision in presenting a hologram form of the president. New Media, with all its derivation is used by the president to dissemination message he made. This research paper is a literature review with the main data sources are books on communication style theory and leadership, as well as theories about new media technology. The secondary of materials used is a variety of reports about Jokowi communication activities to the Millenials. With the concept of diffusion of innovation, this hologram innovation in government area needs to be appreciated, as well as to be measured on how the audiences perspective towards the technology adaptation in the event.